Transactions on Data Hiding and Multimedia Security IV - Shi, Yun Q. (Transactions on Data Hiding and Multimedia Security, 2009)
Since the mid 1990s, data hiding has been proposed as an enabling technology for securing multimedia communication, and is now used in various applications including broadcast monitoring, movie fingerprinting, steganography, video indexing and retrieval, and image authentication. Data hiding and cryptographic techniques are often combined to complement each other, thus triggering the development of a new research field of multimedia security. Besides, two related disciplines, steganalysis and data forensics, are increasingly attracting researchers and becoming another new research field of multimedia security. This journal, LNCS Transactions on Data Hiding and Multimedia Security, aims to be a forum for all researchers in these emerging fields, publishing both original and archival research results. This fourth issue contains five contributions in the area of digital watermarking. The first three papers deal with robust watermarking. The fourth paper introduces a new least distortion linear gain model for halftone image watermarking and the fifth contribution presents an optimal histogram pair based image reversible data hiding scheme.